Immune modulation of parasite transmission in Plasmodium vivax malaria. Anti-gamete antibodies can both block and enhance transmission - Mendi, Kamini N.; Peiris, J.S.M.; Premawansa, Sunil; Udagama, Preethi V.; Munesinghe, Yamuna; Ranawaka, Maya; Carter, Richard; David, Peter H. (Molecular Strategies of Parasitic Invasion, pages 417-426, 1987)
Antibodies directed against Plasmodium vivax gametes can block the development of the parasite in the mosquito vector and interrupt transmission. Usi ng monoclonal antibodies we have defined two components of molecular weights 36 and 42-kilo Daltons as target antigens of transmission-blocking immunity in this parasite. A high level of transmission-blocking activity can be detected in the sera of P.vivax infected individuals Anti gamete monoclonal antibodies, as well as antibodies in immune human sera, can have two opposite effects on transmission, blocking and enhancing.
Keywords: Plasmodium vivax; immune modulation; parasite; anti-gamate antibodies